PENENTUAN JENIS TUMBUHAN LOKAL DALAM UPAYA MITIGASI LONGSOR DAN TEKNIK BUDIDAYANYA PADA AREAL RAWAN LONGSOR DI KPH LAWU DS: Studi Kasus di RPH Cepoko Determination of Local Plants Species in Mitigation Effort at Areas Prone and Cultivation Techniques .... - Fibo Adhitya; Omo Rusdiana; Muhammad Buce Saleh (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2017)
Natural disasters that occur in most areas of Indonesia would certainly give rise to a wide range of impacts on the physical, social, and economic life of the society. One of these natural disasters is landslides. KPH Lawu Ds is a owned company Perhutani, which produces pine resin. KPH area Lawu Ds are generally located in areas that have a steep slope has an area prone to landslides are quite extensive. Therefore, in carrying out forest cultivation of plants which are generally homogenous need additional types of vegetation can reduce the level of vulnerability to landslides. Landslides can also be regarded as a form of land use that have little or no attention to soil conservation techniques, but in this study only look from the vegetation in developing soil conservation techniques in homogeneous plantation forests in the forest management unit areas KPH Lawu Ds. Therefore, the purpose of this study was to obtain the right local plant species as the plant are prioritized and appropriate to prevent the occurrence of landslides and obtain the shape and pattern of cultivation. Data analysis using descriptive analysis of qualitative and models that fit the preferences of local preferences of plants grown on land prone to landslides in RPH Cepoko by using the method of AHP (Analytical Hierarchy Process). Alternatives are obtained based on the plants prioritized is clove, coffee, chocolate, calliandra, Leucaena leucocephala, durian, Swietenia macrophylla, Aleuriteus Moluccana, Paraserianthes falcataria, Pangium edule, Anacardium occidentale , and Sterculia foetida and cultivation techniques of forest vegetation on the sides of the plant adjusted based onsolum soil, slope and vegetation cover of pine with dense composition, middle and rare on research plots in the area of KPH Lawu Ds and planting distance is determined by the density of the canopy.Key words: mitigation, native plant species, preference, cultivation techniques.